EMPIRICAL RESEARCH OF THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY (CSR) TOWARDS THE CORPORATE IMAGE EVIDENCE FROM LQ45 INDEX COMPANIES - Michael Evan; Dominique Razafindrambinina (Journal of Business Strategy and Execution, 2015)
The objectives of this study is to examine the effect of corporate social responsibility on Corporate Image in Indonesian companies based on LQ45 index which denoted by corporate image as dependent variable, CSR as independent variable, Return on Equity (ROE), Stock Price, Asset Turnover (ATO), and Company Size as the control variables. This study uses 43 companies listed in LQ45 Index for the period of 2010-2013 as the sample. Two companies does not have a complete annual report for 2010 and 2011, therefore, those 2 companies are removed from this research. The data analysis used is correlation analysis and multiple regression analysis. This study finds that Corporate Social Responsibility (CSR) has positive and significant effects towards Corporate Image (CI). The results for control variables show that Asset Turnover (ATO), Stock Price (SP), Return on Equity (ROE), and Company Size have no effect on Corporate Image. Corporate Social Responsibility (CSR) positively and  affects significantly Corporate Image ,while Stock Price, Asset Turnover, Company Size, and Return on Equity showed no effect on Corporate Image. If companies in Indonesia want to have a positive public perception from societies, Corporate Social Responsibility (CSR) is one of the appropriate program that could be implemented within the company.